Reseña de: De Lázaro Torres, María Luisa y Morales Yago, Francisco José (2021). Introducción a la Investigación en Geografía. Pautas para la Elaboración de Trabajos Científicos. (An Introduction to Research in Geography. Guidelines for the Preparation of Scientific Papers) - Fernández Portela, Julio (Espacio Tiempo y Forma. Serie VI, Geografía, 2021)
Reseña de: De Lázaro Torres, María Luisa y Morales Yago, Francisco José (2021). Introducción a la Investigación en Geografía. Pautas para la Elaboración de Trabajos Científicos (An Introduction to Research in Geography. Guidelines for the Preparation of Scientific Papers). Madrid: UNED, 223 pp., ISBN: 978-84-362-7689-3.